TADRIS MAHARAH AL-QIRA'AH FI DLAU AL-MADKHAL AL-BINA'I AL-IJTIMA'I - Alawiyah, N. Lalah (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2014)
Social constructivism, which is often called Vygotsky’s constructivist theory, is the latest teaching and learning approach which emphasizes on the importance of culture and social context or social interaction for knowledge development. Social constructivists view learning not only as individual process but also as a social process. Guided with social constructivism, this article aims to discuss its application in reading teaching. The implication of the models of learning recommended based on social constructivism are collaborative learning, cooperative learning, peer-scaffolding, reciprocal teaching, and contextual learning. DOI: 10.15408/a.v1i2.1145